(untitled) (International Journal of Engineering and Computer Science, 2014)
During transmission the different types of noise that are either in the image during captured or injected in to the image. When captured images usually have Gaussian noise, Speckle noise, and Salt and pepper noise. To remove these types of noise applied image filtering methods on images. In this paper, four different image filtering methods are compared using the Peak Signal to Noise Ratio (PSNR) and Mean Square Error (MSE) for the three different noise types. The median filter gives desirable results in terms of the above parameters for three different noises